Discrimination against Islam in America: A Comprehensive Analysis - Galvin Helen (GoAcademica Research & Publishing, 2023)
This journal article examines the phenomenon of discrimination against Islam in the United States. The rise of Islamophobia and instances of bias against Muslims have garnered significant attention in recent years. This paper delves into the historical roots, manifestations, causes, and consequences of this form of discrimination. By exploring various case studies, legislative measures, and social attitudes, the article aims to provide a comprehensive analysis of the challenges faced by the Muslim community in America and suggests potential avenues for addressing this issue.